HUBUNGAN PERSONAL HYGIENE DENGAN GEJALA DERMATITIS KONTAK IRITAN PADA PEKERJA LAUNDRY KONVENSIONAL DI KELURAHAN SUMBER JAYA KECAMATAN SIANTAR MARTOBA - Tarigan, Usaha Satria Pratama (Jurnal Penelitian Kesmasy, 2025)
The changing lifestyle of people who prefer laundry services to cleaning their own dirty clothes has made this business grow very rapidly, especially in big cities. Irritant contact dermatitis is an inflammatory skin condition caused by disruption of the skin barrier combined with activation of the innate immune response by external or environmental factors. Irritant contact dermatitis ranks first with 80%, allergic contact dermatitis ranks second with 14% to 20%. This study aims to determine the relationship between personal hygiene and symptoms of irritant contact dermatitis in conventional laundry workers in Sumber Jaya village, Siantar Martoba sub-district in 2024. This type of research is quantitative research with an analytical survey design with a cross-sectional study. The sample in this study were 66 laundry workers. The instrument used in this study was a questionnaire. Based on the results of the chi-square test conducted, the results of this study reveal that, there is a relationship between Personal Hygiene and symptoms of irritant contact dermatitis with a p-value = 0.009 (p <0.05) with OR = 4.418 which means the relationship between the two variables is weak. Laundry workers are expected to better maintain personal hygiene after and before carrying out activities.